Luminescent magnets: hybrid supraparticles of a lanthanide-based MOF and ferromagnetic iron oxide by assembly in a droplet via spray-drying. Issue 3 (20th December 2021) - Pujales-Paradela, Rosa; Granath, Tim; Seuffert, Marcel T.; Kasper, Thomas; Müller-Buschbaum, Klaus; Mandel, Karl
Abstract : Herein, we report on the successful creation of a luminescent micron-sized magnet. Abstract : Herein, we report on the successful creation of a luminescent micron-sized magnet. A spray-drying approach was employed to do "chemistry in a droplet" in order to achieve opto-magnetic hybrids in form of micron-scaled particles in a fast and easy way in a single step. This is possible by combining preformed nanoparticles, rare earth metal salts and organic precursors, ultimately leading to nucleation and crystallization of a crystalline lanthanide-based metal-organic framework (MOFs) entangled with the preformed ferromagnetic iron oxide nanoparticles (FIONs). Overall, a truly entangled and stable hybrid is obtained, which combines magnetic and optical properties simultaneously (luminescent magnet) and allows for a completely free choice of the ratios of the constituents and thus flexible and stepless property tuning. On the one hand, the material system that is exemplarily shown herein exhibits very interesting properties. On the other hand, the synthesis and assembly strategy serve as an example for various and more exotic property combinations that can easily be achieved and provides a new generation of truly tunable hybrids, which can be perfectly designed for use in many applications.